1997
DOI: 10.5914/tropocean.v25i1.2725
|View full text |Cite
|
Sign up to set email alerts
|

Zooplâncton Oceânico entre os Estados do Ceará e Pernambuco, Brasil.

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
3
1
1
Order By: Relevance
“…Thus, freshwater flux fertilizes the very coastal area under 10 m depth. Other authors for Northeastern Brazil (e.g., Gusmão et al, 1998;Neumann-Leitão et al, 1999, 2008Campos et al, 2017) registered this same pattern. The constant northeast tradewinds and arid climate in this area permits for the establishment of widespread beaches and dunes, which are in continuous movement due to the absence of anchoring vegetation (Mabesoone and Coutinho, 1970).…”
Section: Discussionsupporting
confidence: 63%
“…Thus, freshwater flux fertilizes the very coastal area under 10 m depth. Other authors for Northeastern Brazil (e.g., Gusmão et al, 1998;Neumann-Leitão et al, 1999, 2008Campos et al, 2017) registered this same pattern. The constant northeast tradewinds and arid climate in this area permits for the establishment of widespread beaches and dunes, which are in continuous movement due to the absence of anchoring vegetation (Mabesoone and Coutinho, 1970).…”
Section: Discussionsupporting
confidence: 63%
“…Most of the copepods species observed in this study were previously reported for the oceanic waters of Brazil (Gusmão et al 1997, Lopes et al 1999, Cavalcanti and Larrazábal 2004, Dias et al 2010, the west-central Gulf of Mexico (López-Salgado et al 2000), the eastern tropical Pacific (northwestern Mexican coast) (Suárez-Morales et al 2000), the Mediterranean Sea and the North Atlantic (Andersen et al 2001(Andersen et al , 2004, and the eastern tropical Atlantic Ocean from 6°S to 4°N and at 6°W, 12°W, 18°W, and 24°W (Piontkovski et al 2003). Small calanoids were dominant at 1 m (smaller calanoids) and large calanoids (like C. carinatus) at 800 m during both sampling periods.…”
Section: Hydrography Conditionsmentioning
confidence: 61%
“…According to Deevey and Brooks (Deevey and Brooks, 1977) and Webber and Roff (Webber and Roff, 1995), a vertical discontinuity in zooplankton abundance can take place in TW, since larger copepods occur mainly in phytoplankton-rich deep waters, whereas smaller species are more numerous at the surface. Nevertheless, studies by Gusmão et al (Gusmão et al (1998) from 100 and 50 m to the surface showed higher biodiversity and abundance in deeper layers around 100 m, where Medeiros et al (Medeiros et al, 1999) found higher primary productivity. For the same area, Neumann-Leitão et al (Neumann-Leitão et al, 1999) confirmed higher biodiversity and productivity from samples from the upper 150 m. In our study, no difference (P .…”
Section: Discussionmentioning
confidence: 94%